EFFECTS OF RECIPROCAL LITERACY TEACHING ON STUDENTS’ RETENTION - Iram Naz,Samreen (IJLTP, 2024)
Reciprocal literacy teaching (RLT) takes place as an educational activity that involves a discussion between the teacher and the students through which the challenges of low-attention and less-comprehension ability are met successfully. The purpose of the study was to determine how reciprocal literacy teaching (RLT) affects secondary school students' retention of physics knowledge. Four strategies predicting, clarifying, questioning, and summarizing were used in rotation in this strategy. Two groups were included in the quasi-experimental design that was utilized for this objective. While the control group received standard therapy, the experimental group had an unusual course of RLT. 118 pupils from four secondary schools for girls were chosen as a sample, out of the 12696 girls enrolled in 38 Girls High Schools in Tehsil Nowshera. A retention test was administered after one month of the achievement test. The experimental and control groups were delayed-tested, and inferential statistics such as the t-test, and descriptive statistics were used to determine the significance of RLT by comparing the two groups. While substantial differences between the experimental and control groups were noted and discovered that the inclusion of RLT had more impact on students' growth of retention than the previous therapy. The implementation of the RLT-method was strongly advised for improving student retention. Pre and Post training for teachers may be provided to integrate RLT into the classroom setting.